Carbon Footprint of Apostichopus japonicus Cultivation Based on Marine Bottom-sowing: A Case in Shandong Province, China - Lin Yang; Dong An; Yuhu Cui; Xuexiu Jia; Dong Yang; Mengqi Sun; Wensheng Li; Yanliang Wang; Longjie Wu (Chemical Engineering Transactions, 2023)
Marine aquaculture, with the potential of reducing greenhouse gas emissions and increasing carbon sink, has become an important carrier to cope with resource and environmental constraints and promote the low-carbon transformation of the global economy. This study aims to estimate the carbon footprint of fresh Apostichopus japonicus based on marine bottom-sowing cultivation technologies in the coastal area of Shandong Province, which has the main Apostichopus japonicus production in China. The aim of the study is to gain a deeper understanding of the hotspot of greenhouse gas emissions at each stage of Apostichopus japonicus production and to provide scientific and technological support for the establishment of targeted emission reduction technologies. Results showed that in the whole process of marine bottom-sowing cultivation, the growing seedling process has the highest carbon dioxide emission of 3,138.5 kg CO2eq per t, accounting for 53.7 % of the total emission. The second highest carbon-emission stage is the pond cultivation process, which is 2075.0 kg CO2eq per t, accounting for 35.5 % of the total emission. The reproductive process and finished Apostichopus japonicus feeding process have the lowest carbon dioxide emission, with contributions of 8.3 % and 2.5 % to the total emissions. Electricity consumption is the largest contributor to the life cycle emissions of fresh Apostichopus japonicus production based on the marine bottom-sowing.